Determining the role of student self-government bodies in the management of a higher educational establishment - Yeriomenko, O.; Krivenko, Yu. (Problems of Engineer-Pedagogical Education, 2019)
The problem of the formation of modern society and the reform of the higher educational system in Ukraine based on the development of student self-government is actualized in this article. Under the conditions of modern life, the need for socialization and democratization of the society and the necessity of educating young people in respect of democratic values are gaining more and more importance. It is emphasized that student self-government forms the future elite of the nation, reveals and educates potential leaders, allows mastering managerial skills. In the course of the research, the concept of "student self-government" is defined as a form of the organization of management of various activities carried out for and by students on the principles of freedom, equality, and direct participation in guiding students’ activities. On the basis of the analysis of domestic and foreign experience, it has been established that active cooperation between student selfgovernment bodies and the administration of higher educational establishment allows solving topical problems of organizing students’ educational space at the legislative level having sufficient authority. The result of the scientific research is to highlight areas of cooperation between student self-governance and the administration of a higher educational establishment.